THE INFLUENCE OF ETHICAL AWARENESS, ETHICAL CONSUMPTION LITERACY, COGNITIVE DISSONANCE, SOCIAL NORMS, AND SOCIAL MEDIA USE ON FAST FASHION CONSUMPTION BEHAVIOR AMONG MILLENNIALS - Ariany Rizky Emor; Dewi Juwita Niaty; Putri Chairunisa; Roza Marsaulina Sibarani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the factors influencing Fast Fashion Consumption Behavior among Millennials in the Greater Jakarta area (Jabodetabek) by integrating ethical, psychological, social, and digital perspectives. Specifically, the research investigates the effects of Ethical Awareness, Ethical Consumption Literacy, Cognitive Dissonance, Social Norms, and Active Social Media Use on Fast Fashion Consumption Behavior. A quantitative explanatory research design was employed using purposive sampling, resulting in 205 valid respondents who met the predefined screening criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that both Ethical Awareness and Ethical Consumption Literacy have significant negative effects on Fast Fashion Consumption Behavior, indicating that stronger ethical cognition is associated with reduced fast fashion consumption. Both constructs also significantly and positively influence Cognitive Dissonance, with Ethical Consumption Literacy emerging as the strongest predictor. Cognitive Dissonance, in turn, exerts a significant negative effect on Fast Fashion Consumption Behavior and significantly mediates the relationship between Ethical Consumption Literacy and consumption behavior, whereas the mediating path originating from Ethical Awareness is not significant. Social Norms exhibit a significant positive direct effect on Fast Fashion Consumption Behavior, while Active Social Media Use and both moderating effects are found to be insignificant. These results indicate that ethical knowledge and the psychological discomfort it generates can meaningfully discourage fast fashion consumption, while also underscoring the persistence of the value–behavior gap in specific pathways. The study contributes to the sustainable consumption literature by distinguishing Ethical Awareness from Ethical Consumption Literacy and providing a more comprehensive understanding of fast fashion consumption among Millennials.